EXPLORING STRATEGIES FOR EFFECTIVE CLASSROOM MANAGEMENT IN LANGUAGE LEARNING ENVIRONMENTS (Academicia Globe: Inderscience Research, 2025)
This article examines effective classroom management strategies specifically tailored for language learning environments. By identifying key challenges and proposing solutions grounded in current educational theories and practices, this study aims to enhance the learning experiences of language students. A comprehensive literature review is complemented by empirical data from classroom observations and teacher interviews, leading to actionable insights for educators